1978
DOI: 10.1007/bf01561524
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glucagon in acute and chronic pancreatitis

Abstract: The increased use of glucagon in the treatment of acute pancreatitis led us to study plasma glucagon in 26 patients with acute pancreatitis and 33 patients with chronic pancreatitis. In all patients simultaneous measurements of plasma glucagon, serum amylase, and serum calcium were performed. In acute pancreatitis there was a tendency toward elevated plasma glucagon and low serum calcium levels, but there was no significant correlation between the concentrations of plasma glucagon, serum calcium, and serum amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Other reports of this etiology either fail to measure glucagon or report low glucagon levels as would be expected in chronic pancreatitis. 6,16–18 Therefore, our patient's elevated glucagon level may have contributed to her NME presentation. In patients with normal glucagon levels, it is speculated that NME skin findings are mediated by enteroglucagon rather than glucagon, a substance that is produced by the crypt cells of the small intestine in the malabsorptive state.…”
Section: Answermentioning
confidence: 87%
“…Other reports of this etiology either fail to measure glucagon or report low glucagon levels as would be expected in chronic pancreatitis. 6,16–18 Therefore, our patient's elevated glucagon level may have contributed to her NME presentation. In patients with normal glucagon levels, it is speculated that NME skin findings are mediated by enteroglucagon rather than glucagon, a substance that is produced by the crypt cells of the small intestine in the malabsorptive state.…”
Section: Answermentioning
confidence: 87%
“…We did however identify documented associations between elevated circulating glucagon concentrations and a range of medical conditions. These include diabetes mellitus ( 46 48 ) [including gestational diabetes ( 49 )], acute and chronic pancreatitis ( 50 , 51 ), chronic kidney disease (including that associated with type 2 diabetes mellitus) ( 52 , 53 ) and liver cirrhosis ( 54 56 ). Small studies have also suggested potential associations with hyperthyroidism ( 57 ) and the second trimester of pregnancy ( 57 ), although these findings have not yet been independently verified to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The glucagon level decreased in both groups after surgery. This seems to be due to the removal of the inflammatory activity in the pancreas which is responsi ble for an elevated glucagon level in acute attacks of chronic pancreatitis [40,41], Glucagon elevates the blood glucose level so that this effect should have a positive influence on the blood glucose level. However, the major difference between the surgical procedures is, in fact, the preservation of the duodenum and this appears to be the crucial factor for intact or unchanged glucose tolerance after duodenum-preserving resection.…”
Section: Discussionmentioning
confidence: 99%